PENGARUH BUDAYA KERJA, MOTIVASI KERJA, ETOS KERJA DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KINERJA PEGAWAI STIE AUB SURAKARTA - Sundari . (KELOLA, 2015)
The result of multiple linear regression analysis that the variable use of information technology is the most dominant influence on employee performance, with a value of 0.362. T-test results known significant value of each variable of work motivation, work ethic and utilization of information technology smaller than significant level, which means significantly. While working culture variables obtained sig. 0.562> a significant level of  (0.05) which means insignificant. F-test is based on the results of data analysis known Fhitung = 50.835, which means that simultaneously there is a significant influence. R2 test result was 0,879, meaning the ability of the work culture variable, work motivation, work ethic and utilization of information technology in explaining variable employee performance amounted to 87.9%, while the remaining 12.1% is influenced by other variables that are not described in this model, among others, the working environment and leadership. Keywords: work culture, work motivation, work ethic, utilization of information technology and performance